Review of Acupuncture and Moxibustion Treatment of Neurogenic Bladder after Spinal Cord Injury - Qianqian LIN; Chengmei LIU; Kewei CHEN; Huijie DUAN (康复学报)
This paper summarizes the research status of acupuncture and moxibustion in the treatment of neurogenic bladder(NB)after spinal cord injury(SCI)at home and abroad, mainly from the mechanism of acupuncture treatment of NB after SCI, the application of acupuncture methods, characteristics of acupoints selection, treatment timing, selection of outcome indicators, etc. Acupuncture can promote the proliferation of neural stem cells in patients with NB after SCI, so as to stimulate nerve regeneration and improve the function of the damaged nervous system; it can effectively induce the expression of neurotrophic factors and promote the repair of tissues after SCI; it can reduce the expression of pro-inflammatory and pro-apoptotic factors after SCI, so as to inhibit the apoptosis of nerve cells and protect nerve cells. Acupuncture, moxibustion, acupoint injection and comprehensive therapy were commonly used in the treatment of NB after SCI.In the acupuncture and moxibustion treatment of NB after SCI, acupoints selection mostly follow the principle of meridian selection and local acupoint selection. There is no unified understanding about the time window selection of acupuncture treatment NB after SCI.Most studies believe that the urination system temporarily loses the control of the central system after spinal cord injury, but it is not completely damaged. Early acupuncture treatment can maintain certain sensory impulse stimulation in the region, which can provide a good basis for the later reconstruction of reflex urination. The main outcome indicators of acupuncture treatment NB after SCI should be the difference of urination function before and after treatment, mainly including 24-hour average urination frequency, leakage frequency, voiding volume and incontinence frequency, intermittent catheterization frequency and standardized urine pad test, etc. Secondary outcome indicators include urodynamics, quality of life, treatment efficiency, safety outcome indicators, etc. However, there are still some controversies about the scientificity of clinical efficacy evaluation, which mainly includes the following aspects: the evidence-based evidence is not strong, randomized controlled trials are not strictly carried out, the baseline of research objects is unbalanced, the evaluation tools are lack of specificity, and the registration procedures of clinical trials are not standardized. In the next step, we should carry out multi center, large sample and strict randomized controlled trials, improve the registration procedures of clinical trials, scientifically and reasonably select appropriate acupuncture treatment programs according to the classification of patients with NB after SCI, and explore scientific and objective outcome evaluation indicators, so as to improve the scientificity and credibility of relevant research.